Hukum Tentang Begal Sepeda Motor Di Kota Medan - Citra Sianturi; Feny Christin Silaen; Tira Kania Pardosi; Sri Yunita (Lembaga Pengembangan Kinerja Dosen, 2023)
Law is a rule of rules made to regulate every behavior of the community so as not to carry out deviant activities. One of the actions that deviate from the norms of human life association is social problems, namely problems that occur in society where the perpetrators and victims are the people themselves. One of the deviant actions from the community is the crime of beheading where this beheading began to be rife in the Medan city area. The problem that has recently paraded the streets is often termed Begal. This begal is one of the street crimes, which has recently received serious attention from the public and law enforcement officials. This research was conducted using descriptive qualitative research and using direct interview techniques to police investigators for beheading crimes. The results showed that from several incidents that were successfully revealed by the police, data could be obtained that the perpetrators of this begal crime came from families with low economic and there was no relationship between low punishment for beheading perpetrators to the increase in beheading cases because the legal sanctions given are aimed at providing accountability for the acts resulting from crimes committed by someone